Distribution of Both Fungi and Bacteria Detected from the Nasal and Oral Cavity (Statistical Survey in Kirkuk) - Sanaa H. Mohammad (Journal of Global Pharma Technology, 2018)
The study was carried out at the period from 1st march 2018 to 31st june 2018 in order to determine the relationship of the allergic fungi with the worker in services and restaurant also university student and study the occurrence of fungi and bacteria detected from nasal and oral cavity among University Students , Restaurant workers and services workers with mean age (47.40±22.14) subjects from different areas of Kirkuk City(107) isolates of bacteria and fungi isolated from the nasal cavity in the same time( 45) isolates of bacteria and fungi isolated from the oral cavity the isolates represented by : A. niger, A. flavus, A. fumigatus, A. nidulans, A. terreus, A. japonicas, A. japonicas, Alternaria spp, C. albicans, C. parapsilosis, Penicillium spp, Rhizopus spp, S.pyogen, S.aureus .The statistical analysis, existence of significant differences at the level of probability (P< 0.05) between the type of isolates the high frequency isolation represented by, A.niger, and S.aureus in the oral and nasal cavity which appeared with high occurrence . The subjects in this study were divided into five age groups. On the other hand the statistical analysis of the existence significant differences (P< 0.05) between the fungal and bacterial isolation infection and age for all age groups, it had been found that the age group 26-35 years was the most influential of these infections, compared with the other age groups.Keywords: Fungi, Bacteria, Nasal and oral cavity